ANALISIS TINGKAT MINAT MEMBACA CERITA FIKSI SISWA DALAM PEMBELAJARA BAHASA INDONESIA - Nabela, Indirawati; Rohani; Aulia Sunarti Cikal Putri; Alma Farida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Interest in reading is one of the important factors in supporting the success of learning Indonesian, but there are still students who show varying interest in reading. This study aims to find out the level of interest in reading students' fiction stories in learning Indonesian. The method used was quantitative descriptive with a subject of 20 students at SDN 2 Dungusiku. The data collection technique used a closed questionnaire based on reading interest indicators, while data analysis was carried out by descriptive statistical techniques. The research instrument has been tested for validity and realism. The results of the realism test using Cronbach's Alpha with the help of SPSS 2021 obtained a value of 0.925 which shows that the instrument is in the category of reliability and suitable for use in the research. Based on data analysis, the range of reading interest scores is classified into four categories, namely high, high, medium, and low. The results of this study show that students' interest in reading fiction stories in learning Indonesian is dominated by the timggi category by 75%, while 25% is in the medium category. These findings indicate that students have good interest, attention, and involvement in reading fiction stories. Thus, students' interest in reading fiction fiction in learning Indonesian is relatively high and contributes positively to supporting Indonesian language learning.